Use of Elastics in Orthodontics. (2nd April 2022) - Vesey, Jennifer; Dillon, Maria; Chadwick, Stephen; Edwards, Ian
Abstract : Intra-oral elastics are commonly used during orthodontic treatment and may be applied to several different clinical situations. They are useful for moving individual teeth, blocks of teeth and aiding growth modification. This article reviews the theory behind the use of intra-oral elastics and illustrates the theory with clinical examples. CPD/Clinical Relevance: Elastics are an essential adjunct to orthodontic treatment and have numerous clinical applications.